2007
DOI: 10.1007/s00392-007-0521-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into an old controversy

Abstract: Coronary artery ectasia (CAE) is defined as a localized or diffuse non-obstructive lesion of the epicardial coronary arteries with a luminal dilation exceeding 1.5-fold the diameter of the normal adjacent arterial segment. The incidence of CAE has been reported to range between 2% and 4%, which might be an overestimation of the true frequency. The coincidence of CAE with other systemic vascular dilatations has suggested that the mechanism underlying CAE is not only localized to coronary arteries, but also to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 90 publications
2
35
0
Order By: Relevance
“…18 This study also found a statistically significant relation between CAE and IIEF-5 score, confirming all the studies above. In conclusion, however atherosclerosis is one of the responsible mechanisms in CAE, actual cause of ectasia is unknown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…18 This study also found a statistically significant relation between CAE and IIEF-5 score, confirming all the studies above. In conclusion, however atherosclerosis is one of the responsible mechanisms in CAE, actual cause of ectasia is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…18 Histopathological characteristics of CAE are similar to those of coronary atherosclerosis, so it is not surprising that hypotheses for the origin of CAE revolve around the vascular endothelium and the biological properties of the arterial wall. Nevertheless, the specific causative mechanism of abnormal luminal dilatation in CAE remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed that 50% of patients with CEA also have concomitant atherosclerosis [9], with a most frequently involved branches of RCA, followed by LAD and LCX [2,4], while ectasia of multivessels and LM were rare [9]. However, CEA with atherosclerosis only occurred in 28% of the present study, while isolated CEA were observed in more than 70% patients, strongly supporting a recent viewpoint that CEA was not a simple variant of atherosclerosis [10]. Moreover, LAD is the most commonly involved artery, multiple coronaries and LM involvement observed in about 2/3 and 1/4 patients in the present study, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have evaluated the traditional cardiovascular risk factors in patients with CAE, and male dominance, younger age, hypertension, dyslipidemia, smoking, cocaine use, low prevalence of diabetes and persisting congenital anomaly, which included bicuspid aortic valve, aortic root dilatation, ventricular septal defect, pulmonary stenosis or cyanotic congenital heart disease have been implicated [6]. Th e frequent coexistence of CAE with CAD and histopathological fi ndings resembling those of atherosclerosis have led to the conclusion that the mechanism underlying the pathogenesis of CAE is a variant of atherosclerosis but there are some diff erences between CAE and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, CAE is found to coexist with CAD, whereas in 10-20 of cases, it is associated with cocaine abuse, toxins, infl ammation, infections, infl ammatory diseases, cardiac lymphoma and connective tissue disorders such as Kawasaki disease, systemic lupus erythematosus, Marfan syndrome, and Ehlers-Danlos syndrome [6][7][8][9][10]. In histopathological appearance of the disease, marked destruction and reduction of the medial elastic fi bers with disruption of the internal and external elastic lamina, smooth muscle hyalinization of the coronary fi bro-muscular media, excessive nitric oxide (NO) production which leads to hyalinization by indirect acetylcholine production have been found [6][7][8][9][10]. Severe coronary wall infl ammation may play a role in CAE pathogenesis [10,11].…”
Section: Introductionmentioning
confidence: 99%